Orientation dependence of stored energy of cold work in semi-processed electrical steels after temper rolling - Castro, S. F.; Gallego, J.; Landgraf, F. J. G.; Kestenbach, H. J. (Elsevier B.V., 2006)
Microhardness measurements were carried out in a low carbon lamination steel after 6% of temper rolling, in order to evaluate local variations of work hardening as a function of crystallographic orientation. EBSD (electron back scattered diffraction) was used to determine grain orientations with respect to individual rolling planes and rolling directions. Hardness was shown to increase with the local Taylor factor. TEM observations and a well-known dislocation hardening model were used to confirm the equivalence between hardness values and the stored energy of cold work. A definite correlation between stored energy and Taylor factors could therefore be established, being more consistent than previous data reported in the literature. The improvement was thought to be related to the rather small plastic deformation, during which Taylor factors could be considered to remain constant. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: electrical steels; plastic deformation; stored energy; Taylor factors